(untitled) (Plant Tissue Culture and Biotechnology, 2010)
Flavonoids baicalein and baicalein-7-o-glucoside were estimated in in vitro raised (six months old) as well as nature grown (12 months old) plants of Oroxylum indicum (L.) Vent. Multiple shoot formation and elongation were obtained from axillary and apical bud explants of O. indicum on MS containing BAP (1 mg/l) and AgNO3 (2 mg/l). Rooting of the regenerated shoots was achieved on medium (half strength) containing IBA (1 mg/l) and AgNO3 (1 mg/l). A quantitative HPLC analysis of methanolic extract of leaf and root indicated the enhancement of baicalein-7-o glucoside in in vitro raised root and leaf of Oroxylum indicum. Key words: Assessment, Secondary metabolites, Regenerated plantlets, Oroxylum indicum D.O.I. 10.3329/ptcb.v20i1.5961 Plant Tissue Cult. & Biotech. 20(1): 21-28, 2010 (June)